The Effect of Valvular Heart Disease on Maternal and Fetal Outcome of Pregnancy in Young Pregnant Females - Asia Altaf, Saira Faiz, Samson S. Badalyan, Ramsha Khan, Sheherbano Yahya (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The objective of this study is to determine the effect of valvular heart disease on maternal and fetal outcomes of pregnancy in young pregnant females Study design: Retrospective study Methodology: A retrospective study was conducted to get an analysis of 321 healthy women and 312 women with valvular heart disease who received care at a tertiary care hospital during the same time period and compared the results of their pregnancies. The chi (2)-test was used for statistical analysis, with a significance set at 0.05. Results: n comparison to women in the control group, women with valvular heart disease had significantly higher rates of congestive heart failure (5.1 percent vs. 0 percent, P0.001), mortality (0.64% [two women] vs. 0 percent), and surgical interventions during pregnancy (13.4 percent (balloon mitral valvotomy) vs. 0.6 percent [ovarian cystectomy Additionally, the perinatal outcome was worse in the valvular heart disease group than in the control group, with higher preterm delivery rates (48.3 percent vs. 20.5 percent), lower birth weights (2434+/-599 g vs. 2653+/-542 g; P0.001), and a higher incidence of APGAR scores below 8 (8.3 percent vs. 4 percent; P0.01). Additionally, the rate of instrumental delivery increased (9.9 percent vs. 3.4 percent). The proportion of cesarean deliveries, however, was comparable across the two groups. Conclusion: In conclusion, there is a substantial link between valvular heart disease and maternal and neonatal mortality. Close fetal and maternal monitoring are required, and valvular stenosis should be repaired before conception. To avoid difficulties for both the mother and the fetus, balloon valvuloplasty should be taken into consideration in cases of severe stenosis during the second trimester of pregnancy. The hospitals that deal with heart illness and pregnancy should create practical recommendations. Keywords: Valvular heart disease (VHD), Pregnancy outcome; maternal outcome; Fetal outcome, young pregnant.